Up regulation of the Epstein-Barr virus (EBV)-encoded membrane protein LMP in the Burkitt's lymphoma line Daudi after exposure to n-butyrate and after EBV superinfection. - Contreras-Salazar, B (1990)
The Burkitt's lymphoma line Daudi carries a nontransforming Epstein-Barr virus (EBV) strain that has a deletion in the BamHI WYH region of the genome coding for the EBV nuclear antigen 2 (EBNA-2). Daudi cells fail to express the EBV-encoded latent membrane protein (LMP) (D. Ghosh and E. Kieff, J. Virol. 64:1855-1858, 1990). We show that LMP expression can be up regulated by exposure to n-butyrate and by superinfection with the B95-8 (B virus)- and P3HR1 (P virus)-derived EBV strains. Two LMP polypeptides of 60 and 48 kilodaltons (kDa) were detected in immunoblots of Daudi cells that had been exposed to 3 mM n-butyrate for 24 h. The intensity of the 48-kDa LMP increased during 72 h, in parallel with the appearance of early antigen-positive cells. The 60-kDa LMP was expressed at a low level and remained constant. Superinfection of Daudi cells with B and P virus induced the 60-kDa LMP within 3 h. In addition, P virus induced the 48-kDa LMP at a low level. The B virus-encoded EBNA-2 and EBNA-5 were detected 12 h after superinfection. The B virus-encoded 63-kDa LMP was coexpressed with the endogenous LMP after 48 h. Inactivation of the virus by UV illumination abolished the expression of the B virus-encoded antigens but did not affect the induction of the endogenous LMP. The B-cell activation marker CD23 was up regulated by B virus superinfection but not by n-butyrate exposure. CD23 was also expressed at a higher level in a stable B virus-converted subline, E95A-Daudi, that was EBNA-2 positive and coexpressed the Daudi virus- and B virus-encoded LMP. The results suggest that LMP expression is regulated by the interaction of cellular and viral factors. Binding of the virus to its membrane receptor might be involved in the triggering of cellular control mechanisms. Viral gene products are not directly involved in this function but may contribute to create a permissive cellular environment for LMP expression.